2004
DOI: 10.5737/1181912x144224227
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the journey of cancer patients through the health care system. Part 2: Methodological approaches and basic findings

Abstract: This is the second in a series of articles from a line of research whose intent was to construct a complete history of interactions with the health care system. This paper provides details of the methods developed to collect and collate the scattered information regarding the event history (trajectory) that a cancer patient experiences in traveling through the Manitoba health care system from one year prior to diagnosis through to two years post-diagnosis. Survival data were obtained through 1994. Basic popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…37 Studies published to date on patient journeys have been limited, providing data from small numbers of research interviews or focus groups. [21][22][23][24]38 The current study, while limited to 300 respondents, represents the largest published examination of women's journeys with hypertension. Results of the current study reinforce themes observed in other studies of patient journeys with cardiovascular disease, including the need for patientcentric communication 24 and the need for health care providers to understand the social constructs that are unique to women's experiences with cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…37 Studies published to date on patient journeys have been limited, providing data from small numbers of research interviews or focus groups. [21][22][23][24]38 The current study, while limited to 300 respondents, represents the largest published examination of women's journeys with hypertension. Results of the current study reinforce themes observed in other studies of patient journeys with cardiovascular disease, including the need for patientcentric communication 24 and the need for health care providers to understand the social constructs that are unique to women's experiences with cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies published to date on patient journeys have been limited, providing data from small numbers of research interviews or focus groups . The current study, while limited to 300 respondents, represents the largest published examination of women's journeys with hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore data linkage methods offer the prospect of tracking patients as their care is delivered through a plethora of administrative and clinical centres each with their own records. Researchers in Canada and Western Australia have notably linked data from multiple sources to address questions such as patterns of use of health services by the older populations [4], the quality of surgical care [5], factors affecting hospital use [6,7], and mapping the journey of cancer patients through the health care system [8]. Data linkage affords critical comparisons across geographical regions, demographic characteristics, and use of hospitals and treatment modalities.…”
Section: Introductionmentioning
confidence: 99%